(3GdJVNe GdEbJUGOj hGdJfejI GdSjGMjI (B/s - (3GdehShj, UaGA YHO GdLHGQs ((3YeGf(B: s (3OGQ GdGjGe(B, s, 2014)
(3jJVef GdJVNe GdGbJUGOj, GdJfejI GdSjGMjI, GdJVNe GdSjGMj, h GdCKGQ GdJVNe GdSjGMj hGdEfYcGSGJg , EfYcGSGJ GdJVNe GdEbJUGOj hGdSjGMj Ydi GdJfejI GdSjGMjI aj GdYdGb hcQHdGA(B.s
(3GdeQGLY U(B.189s
Keywords: (3GdCReGJ GdEbJUGOjIs; (3GdJVNe GdeGdjs; (3JfejI GdSjGMIs